THE ADMINISTRATION AND ADVANCEMENT OF SMALL-SIZED SCHOOLS THROUGH THE USE OF ARTIFICIAL INTELLIGENC - Phonprasert, Siripon (Journal of Educational Review Faculty of Education in MCU, 2025)
In the context of small schools in Thailand—comprising over 50% of all educational institutions nationwide—these schools often face systemic challenges in managing personnel, resources, and operations, particularly in remote areas with limited budgets and insufficient teaching staff. The success of these schools largely depends on the principal’s ability to perform multiple roles, including teaching, administration, and community coordination. Meanwhile, the rise of technology, especially Artificial Intelligence (AI), has increasingly influenced the education sector. UNESCO has proposed an AI competency framework for students, encouraging schools to adopt AI to enhance learning, management, and communication. This article presents a model for applying AI in five key areas: learning management, planning and decision-making, student safety, student support systems, and community engagement. A case study from Wat Ban Lam Nang School under Phichit Primary Educational Service Area Office 1 illustrates how tools like dashboards, chatbots, predictive analytics, and generative AI were used to support data analysis, strategic planning, and parental engagement. The results showed improved learning efficiency, decision-making accuracy, and strengthened community trust. The article advocates for a paradigm shift in small school administration—from traditional management to data-driven systems—with AI serving as a “Smart, Flexible, and Transparent” assistant, promoting lifelong learning among educators and establishing ethical technology policies to ensure sustainable quality education in the 21st century